A case‐controlled comparison of postoperative analgesic dosing between girls with Rett syndrome and girls with and without developmental disability undergoing spinal fusion surgery. Issue 3 (8th February 2017) - Barney, Chantel C.; Merbler, Alyssa M.; Quest, Kelsey; Byiers, Breanne J.; Wilcox, George L.; Schwantes, Scott; Roiko, Samuel A.; Feyma, Timothy; Beisang, Arthur; Symons, Frank J.
Summary: Background: Rett syndrome is associated with severe motor and communicative impairment making optimal postoperative pain management a challenge. There are case reports documenting reduced postoperative analgesic requirement in Rett syndrome. Aim: The goal of this preliminary investigation was to compare postoperative analgesic management among a sample of girls with Rett syndrome compared to girls with and without developmental disability undergoing spinal fusion surgery. Method: The medical records of eight girls with Rett syndrome (mean age = 13.2 years, sd = 1.9), eight girls with developmental disability (cerebral palsy; mean age = 13.1 years, sd = 2.0), and eight girls without developmental disability (adolescent idiopathic scoliosis; mean age = 13.4, sd = 1.8) were reviewed. Data related to demographics, medications, and route of drug administration were recorded. Results: Girls with Rett syndrome received significantly fewer morphine equivalent opioids postoperatively ( M = 0.26 mg·kg −1 ·day −1, sd = 0.10) compared to girls with adolescent idiopathic scoliosis ( M = 0.47mg·kg −1 ·day −1, sd = 0.13; 95% CI −0.34 to −0.08; P = 0.001) and girls with CP ( M = 0.40 mg·kg −1 per day, sd = 0.14; 95% CI −0.27 to −0.02; P = 0.01). Girls with Rett syndrome received significantly fewer opioid patient‐controlled analgesic (PCA) bolus doses (given by proxy; M = 42.63, sd = 17.84) compared to girls with adolescent idiopathic scoliosis ( M = 98.25, sd = 52.77; 95% CI −96.42 to −14.83; P = 0.01). There was also some evidence indicating girls with Rett syndrome received fewer bolus doses compared to girls with CP ( M = 80.88, sd = 38.93; 95% CI −79.05 to 2.55; P = 0.06). On average, girls with Rett syndrome also received smaller total doses of acetaminophen, diazepam, and hydroxyzine. Conclusion: This study highlights possible discrepancies in postoperative pain management specific to girls with Rett syndrome and suggests further investigation is warranted to determine best practice for postoperative analgesic management for this vulnerable patient population. Abstract :